Metformin for neurocognitive dysfunction in schizophrenia: a systematic review - Qin, Zhen-Juan; Shi, Zhan-Ming; Li, Li-Juan; Wei, Xin; Hu, Hui-Lin; Wei, Wei; Xie, Zhi-Yuan; Ji, Hang-Xi; Wei, Yu-Hua; Zheng, Wei (Frontiers in Psychiatry, 2025)
BackgroundThe efficacy and safety of metformin for addressing neurocognitive dysfunction in schizophrenia remain inconclusive. This systematic review evaluates the evidence from randomized controlled trials (RCTs) on the effects of metformin on neurocognitive function in patients with schizophrenia.MethodsA comprehensive search of Chinese databases (WanFang, Chinese Journal Net) and English databases (PubMed, EMBASE, PsycINFO, and Cochrane Library) was conducted to identify RCTs assessing metformin’s impact on neurocognitive outcomes in schizophrenia.ResultsFour RCTs involving 271 patients with schizophrenia were included. Three RCTs (75%) demonstrated significant improvements in neurocognitive function with metformin compared to controls, as assessed by the MATRICS Consensus Cognitive Battery, Repeatable Battery for the Assessment of Neuropsychological Status, and Mini-Mental State Examination, but not the Brief Assessment of Cognition in Schizophrenia. Two RCTs (50%) evaluated metformin's effects on total psychopathology and found no significant differences between groups. Adverse events were reported in two RCTs, with inconsistent findings on decreased appetite and diarrhea. Other adverse events and discontinuation rates were comparable between groups.ConclusionPreliminary evidence suggests that metformin may improve neurocognitive function in schizophrenia. However, further large-scale, double-blind, high quality RCTs are warranted to validate these findings.